Design of Delta Modulated AC - DC Converters - Hannoon, Naeem Mohamed Saleem (1999)
An analysis and implementation of delta modulation (DM) technique in the control of ac-dc converters is studied here in this project. The DM technique offers advantages of easy implementation, continues converter voltage control, and a direct control on the line harmonics. A simple circuit of the delta modulator is proposed, designed and fabricated in the laboratory. This proposed modulation scheme, fundamentally differs from conventional PWM technique, by virtue of its self carrier generating ability. Results of the parametric variation of the modulator are reported. Simulated and experimental results of the single phase DM ac-dc converters validate the analytical results.